PRICE-LEVEL ADJUSTMENTS: FETISH IN ACCOUNTING. - Dein, Raymond C. (The Accounting Review, 1955)
Abstract This article focuses on price-level adjustments. Since 1948 there has been a steady flow of articles on the implications of the price-level changes for accounting reports, by far the larger portion agreeing that these changes had undermined the reliability of the convention financial statements. Between World War I and World War II there had been a very substantial amount of writing with a quite similar import. Expressions of dissatisfaction with conventionally prepared financial statements are widest in periods of rising price levels. At times such as these the detractors of accounting statements bemoan the fact that these statements do not use figures which represent "economic realities," whether asset values, or costs of production, or net income. It is not enough to state an ideal, the approximation of economic income "in accounting terms." The statement that the committee did not attempt to define economic income contains a curious double implication. The purpose of income calculations in practical affairs is to give people an indication of the amount which they can consume without impoverishing themselves.